Implikasi Putusan Mahkamah Konstitusi Nomor 78/PUU-XXI/2023 Tentang Penghapusan Larangan Penyebaran Berita Hoaks Perspektif Maslahah: Implications of Constitutional Court Decision No. 78/PUU-XXI/2023 on the Repeal of the Ban on the Dissemination of Fake News: A Maslahah Perspective - Fatiya Adinda Ruth; Farkhani (SIYASI: Jurnal Trias Politica, 2025)
Freedom of opinion is a fundamental right that has existed since birth and has been recognized nationally to internationally. There is a recognition of the guarantee of the right to freedom of opinion, it is clear that this right must be respected. Nowadays, the scope of freedom of expression of opinions is very wide. Social media is the main source of human beings to share, receive, and channel opinions without any pressure. However, there are still many civilians whose right to expression is silenced. The focus of this research is the birth of the Constitutional Court Decision Number 78/PUU-XXI/2023 as evidence that the shackles of the right to freedom of opinion are still rampant. Where the content of the decision examines several articles that are often used as a basis of reference to silence the right to freedom of opinion which has been clearly recognized and guaranteed by the constitution. The Constitutional Court's decision needs to be further studied regarding the benefits of the results of the decision for the public interest. This research is normative research using a conceptual approach and a case approach. The primary legal materials to support this research are the Constitutional Court Decisions, the Human Rights Law, and other related regulations, while the secondary legal materials are journals related to the benefits. This research shows that the Constitutional Court Decision Number 78/PUU-XXI/2023 has a good impact, unraveling the shackles on the right to freedom of opinion, upholding the legal umbre protection to freedom of opinion, and the decision is beneficial because it provides benefits for everyone and is in accordance with the conditions of maslahah.